Interstitial Lung Disease in Connective Tissue Diseases: Survival Patterns in a Population-Based Cohort - Charlotte Hyldgaard (MDPI AG, 2021)
Objectives: Interstitial lung disease (ILD) is associated with impaired survival among patients with connective tissue diseases (CTDs), but population-based data on the frequency of ILD and pulmonary hypertension (PH) in different CTD subtypes and the impact on survival are sparse. Methods: We included patients with a first-time ICD-10 diagnosis of systemic sclerosis (SSc), mixed connective tissue disease (MCTD), myositis, systemic lupus erythematosus (SLE), or Sjögren’s disease registered in the Danish National Patient Registry between 2000 and 2015. Among these, we identified patients with ILD and PH. Using Kaplan–Meier analysis, we assessed survival for the five subtypes of CTD ± ILD and compared survival among CTD patients overall ± ILD with survival in the general population ± ILD. Results: We identified 11,731 patients with a diagnosis of CTD; 637 (5.4%) had a diagnosis of ILD. The proportion of patients with ILD was higher in SSc (13.4%) and MCTD (9.1%) than in myositis (6.0%), SLE (4.1%), and Sjögren (2.8%). Fifty-one percent were diagnosed with ILD in their fifties and sixties. PH was more frequent in SSc (7.5%) and MCTD (4.1%). Five-year survival was 73.3% (66.7–80.6) in SSc-ILD, 81.0% (69.0–95.1) in MCTD-ILD, 84.7% (77.3–92.9) in myositis-ILD, 83.5% (76.2–91.5) in SLE-ILD, and 84.7 (78.4–91.6) in Sjögren-associated ILD. Survival in CTD-ILD overall was impaired for all age groups compared with CTD alone. Age-stratified survival was comparable between CTD-ILD and ILD in the general population. The survival gap between ILD and non-ILD increased with age. Conclusion: Survival was comparable between different CTD-ILD subtypes and comparable to survival in non-CTD-ILD.